The Development of Computer Based Test Instruments using Wondershare Quiz Creator to Measure HOTS in Temperature and Heat - Istikomah, Isna; Suyatna, Agus; Viyanti, Viyanti; Andra, Doni (FKIP Universitas Lampung, 2021)
This study aims to develop a computer-based test instrument using the valid Wondershare Quiz Creator (WQC) to measure HOTS in temperature and heat material. This study uses research and development research methods and the research design used refers to the research design by Borg & Gall. Data analysis was performed by means of internal validation tests by a team of experts. This test instrument has been tested by experts consisting of the material validation test with a score of 3.10 (valid), construction with a score of 2.88 (valid), and language with a score of 3.63 (very valid). The CBT setting on this product is also very valid with an average score of 3.68. The sig value of the difference in the level of validity and complexity in the types of multiple choice, multiple response, matching, and sequence items obtained was> 0.05, which indicates that there was no difference in the average validity and complexity between the four types of questions at each cognitive level. Keywords: Test instruments, Wondershare Quiz Creator (WQC), HOTS. DOI: http://dx.doi.org/10.23960/jpmipa/v22i1.pp45-51